Arbejdsprøve med smaa selvrensende Tærskeværker til Hestekraft (2 å 3 Heste). - Birk, C. V. (Tidsskrift for Landøkonomi, 2018)
Arbejdsprøve med smaa selvrensende Tærskeværker til Hestekraft (2 å 3 Heste).